7(z+1)=13

Simple and best practice solution for 7(z+1)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(z+1)=13 equation:


Simplifying
7(z + 1) = 13

Reorder the terms:
7(1 + z) = 13
(1 * 7 + z * 7) = 13
(7 + 7z) = 13

Solving
7 + 7z = 13

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 7z = 13 + -7

Combine like terms: 7 + -7 = 0
0 + 7z = 13 + -7
7z = 13 + -7

Combine like terms: 13 + -7 = 6
7z = 6

Divide each side by '7'.
z = 0.8571428571

Simplifying
z = 0.8571428571

See similar equations:

| 9-10x=20x+18 | | 7x-6y=13 | | -8t-3t=-5t-6t | | 9-10x=18x+20 | | 9-10x=5x+20 | | 5x^2+8x=165 | | 2x-2=2(x+7) | | 96=14+14+(6+2(14))+(6+2(14)) | | 0.20x+0.25(70)=23.5 | | 96=14x | | 1/4(2x+8)=4(4-3x)+11 | | x+x+(6+2x)+(6+2x)=96 | | (n-7)(n+3)=0 | | x-45=0 | | 2x-5+2=x+2+y | | x+x+(6+x)+(6+x)=96 | | 6x=-11x+7 | | (s-3)(s-4)=0 | | 5x+9=3+8x-6 | | -7x-10=4x+23 | | 1/8(x-8)=1/16(2x+16) | | 6+4x=66 | | 10-3=1 | | 32=x+x+(2+x)+(2+x) | | 10-3=3 | | 3(k+2)=9 | | 32=(2+x)(x) | | 32=2x+x | | 18-6a=4a-(4a+3) | | 120x-42=14x+35 | | A=0.5(4+6)8 | | I=300(0.14)2 |

Equations solver categories